2015
DOI: 10.1177/0003702815620539
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Confocal Raman Microscopy of Hydrated Early Stages of Bacterial Biofilm Formation on Various Surfaces in a Flow Cell

Abstract: Bacterial biofilms are precursors to biofouling by other microorganisms. Understanding their initiation may allow us to design better ways to inhibit them, and thus to inhibit subsequent biofouling. In this study, the ability of confocal Raman microscopy to follow the initiation of biofouling by a marine bacterium, Pseudoalteromonas sp. NCIMB 2021 (NCIMB 2021), in a flow cell, using optical and confocal Raman microscopy, was investigated. The base of the flow cell comprised a cover glass. The cell was inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Surfaces were exposed to Pseudoalteromonas spp. (OD 600nm = 0.25) in tryptic soy broth/artificial seawater, 3:1 26 for 1 h, then shaken at 150 rpm in fresh medium for 24 h at ambient temperature on an orbital shaker (Ratek). Addition of aqueous crystal violet (0.1%, Sigma-Aldrich) turned the biofilm purple, 26 before extraction into 30% acetic acid to measure absorbance (590 nm).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Surfaces were exposed to Pseudoalteromonas spp. (OD 600nm = 0.25) in tryptic soy broth/artificial seawater, 3:1 26 for 1 h, then shaken at 150 rpm in fresh medium for 24 h at ambient temperature on an orbital shaker (Ratek). Addition of aqueous crystal violet (0.1%, Sigma-Aldrich) turned the biofilm purple, 26 before extraction into 30% acetic acid to measure absorbance (590 nm).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Courtecuisse et al demonstrated the effect of oxygen inhibition in an acrylate photopolymerization system 15 . Smith-Palmer et al used CRM to follow the initiation of biofouling by a marine bacterium in a flow cell 16 . Edwards et al have employed Raman spectroscopy to study curing of a cyanoacrylate system for the forensic enhancement of latent fingerprints 17 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The cross-validation analysis of variance (CV-ANOVA) representing the cross-validation result with p -value = 0. Reference [ 59 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%